Pengalaman Orang Tua dengan Anak Hamil Usia Remaja di Wilayah Kerja Puskesmas Ranomuut - Pangalila, Dewini Wahyuni Pratiwi; Meo, Maria Lupita Nena; Kundre, Rina (Program Studi Ilmu Keperawatan Fakultas Kedokteran Universitas Sam Ratulangi, 2023)
Background. Globally, the prevalence of teenage pregnancy is still high. Teenage pregnancy certainly has an impact on parents who have to bear social sanctions in the form of embarrassment and ridicule from residents because their children have violated societal norms. Aim. This study aims to explore the experiences of parents with teenage pregnant children. Methods. The research design uses a qualitative method with a descriptive phenomenological approach. Data were collected using in-depth interview techniques involving five main informants and two supporting informants obtained through purposive sampling technique, as well as source triangulation. Results. The four main focal experiences of parents who have teenage pregnant children are the parents' adaptation process, the impact of teenage pregnancy, the forms of parental support for children, and the forms of support needed by parents. Discussion: Parents with teenage pregnant children have the same adaptation process even though they are faced with different impacts. In addition, parents also continue to carry out their role to the fullest. Conclusion: The varied experiences of parents with teenage pregnant children certainly require special attention. Proper assistance is needed from health workers who not only focus on teenagers, but also on their parents and can provide proper education to the community and attention from the local government. Keywords: coping mechanisms; parental experience; teenage pregnancy